Fauna edáfica asociada a cultivos hortícolas convencionales de tomate en La Plata (Buenos Aires, Argentina) - Aarmendano, Andrea; Rouaux, Julia; Salazar Martínez, Ana (Instituto de Ecología, A.C., 2018)
Edaphic arthropodofauna reflects the vegetation conditions and the soil functioning, therefore, its study is a useful tool to evaluate the soil crops sustainability. Oribatid mites and collembolan hexapods (mesofauna) as well as beetles and spiders (macrofauna) are permanent, abundant and diverse groups in these systems. They are essential organisms in the soil functioning because they regulate and participate in different stages of the decomposition process. The aim of the study was both, to identify the main components of the meso and macrofauna while a conventional tomato crop was developing its cycle and to propose a possible model of relationships among them which helps to assess positive effects due to healthy practices. The study was carried out in a farm where tomato conventional management was being applied, in the neighborhood area of La Plata city. The fauna was collected during a complete crop cycle from December 2012 to February 2013, using the appropriate procedures for each group. We collected 136 individuals and seven oribatid species, 59 individuals and nine collembolan species, 300 individuals and 12 spider species and 113 individuals and 32 coleopteran species. Among them, Scheloribates praeincisus acuticlava, Tullbergidae sp. 1, Glenognatha lacteovittata, Lycosidae sp. 2, Linyphiidae sp. 4 and Phyrdenus muriceus were the most abundant permanent populations in each group. The poor records of mesofauna indicate that it establishes weak links in the trophic soil network, possibly due to the disruptive effect of conventional management practices. The macrofauna presents the greatest number of individuals and specific diversity, especially spiders, probably by their capacity to move to the adjacent crop areas. It is concluded that the edaphic fauna stable group is principally composed by predators, saprophagous and phytophagous related to the crop, so they belong to the herbivory network more than the detritus one.